2020
DOI: 10.1111/ajd.13433
|View full text |Cite
|
Sign up to set email alerts
|

Expression of survivin and p53 genes in patients with alopecia areata: A case–control study

Abstract: Background Alopecia areata is a common non‐scarring hair loss disorder. It has been generally recognised as a loss of immune privilege leading to an autoimmune attack upon anagen hair follicles. Survivin is one of the apoptosis inhibitor proteins, responsible for apoptosis suppression and cell cycle regulation. Survivin expression has been demonstrated in the matrix and outer root sheath keratinocytes of anagen hair follicles. Survivin overexpression was shown in several autoimmune diseases, and it was postula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…
relatively short follow-up, the low sample size and the long-lasting response to the adalimumab originator at the time of the shift for many patients, the results are in line with previous comparability studies 1,3,4,5 and demonstrate that the biosimilar adalimumab has shown not to be less effective than the originator and the transition to biosimilar adalimumab in psoriasis patients treated with the originator is a safe and effective choice in a real-life setting of moderate to severe psoriasis patients as previously observed in other biologic treatments, in particular infliximab. 6 The only difference we observed was a significant worsening of the assessment of pain in a subpopulation of patients with BMI> 25 between T0 and T1 suggesting the need of further evaluations and objective data, also with a multi-specialist team.
…”
supporting
confidence: 89%
See 3 more Smart Citations
“…
relatively short follow-up, the low sample size and the long-lasting response to the adalimumab originator at the time of the shift for many patients, the results are in line with previous comparability studies 1,3,4,5 and demonstrate that the biosimilar adalimumab has shown not to be less effective than the originator and the transition to biosimilar adalimumab in psoriasis patients treated with the originator is a safe and effective choice in a real-life setting of moderate to severe psoriasis patients as previously observed in other biologic treatments, in particular infliximab. 6 The only difference we observed was a significant worsening of the assessment of pain in a subpopulation of patients with BMI> 25 between T0 and T1 suggesting the need of further evaluations and objective data, also with a multi-specialist team.
…”
supporting
confidence: 89%
“…It is widely claimed as an autoimmune assault against the anagen hair follicles in which T-helper 1 (Th) and Th17 are implicated. 1 IL-36a promotes Th1 and Th17 polarisation, 2 whereas IL-37 represses Th1 and Th17 immune Letter To The Editors responses. 3 The altered expressions of IL-36a and IL-37 were demonstrated in several autoimmune diseases but were poorly investigated in AA.…”
Section: Research Letter Dear Editorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alopecia areata (AA) is an acquired non-cicatricial hair loss disorder affecting 0.1%–0.2% of individuals worldwide [ 1 ]. A collapse of the hair follicle (HF) immune privilege causing a CD8+ cytotoxic T (cT) cell assault against anagen HFs is implicated in AA development [ 2 , 3 ]. However, the precise molecular mechanisms are still poorly established.…”
Section: Introductionmentioning
confidence: 99%